The Effect of Capcut Application on Creative Thinking and Learning Achievement of Grade VI Students in Science Subjects at SDN Tambaksari 04 - Dwi Arianti (Proceedings Series on Social Sciences & Humanities, 2025)
Evaluate the effect of using the Capcut application on Creative Thinking and learning achievement of grade VI students in science subjects at SDN Tambaksari 04, Cilacap Regency. The study was conducted for two weeks, starting from March 13 to July 26, 2024. The research method used was quasi-experimental research, which aims to identify the causal relationship between the use of the Capcut application and the variables studied, by minimizing other factors that might affect the results of the study. Starting from the understanding that technology has the potential to improve the quality of learning, this study highlights the Capcut application as an interesting and innovative learning media. In the context of 21st century learning, where high-level thinking skills are the main focus, the use of technology is considered to be able to stimulate students' Creative Thinking and improve their learning achievement. Through this study, the author hopes to gain a deeper understanding of how the use of the Capcut application can affect Creative Thinking and student learning achievement. The results of this study are expected to provide valuable insights for educators in developing effective and innovative learning strategies, as well as contributing to the development of technology in the context of education.